Pengaruh Insentif dan Gaya Kepemimpinan Terhadap Produktivitas Karyawan di PT. Trans Kreasindo Production Medan - Farhan Zuhdi, Ahmad (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
Lack of appropriate and suitable incentives from factory leaders to their workers and lack of consideration of its influence on the quality and productivity of workers' work, this study focuses on the analysis of the influence of manager motivation and leadership style on employee performance. The purpose of this study was to determine the influence of manager motivation and leadership style on employee productivity. Using SPSS analysis, the regression equation Y = 22.435 + 0.218X1 + 0.398X2 was obtained. From this equation, the leadership variable (X2) is more dominant than the leadership style (X1) in influencing employee work productivity at PT. Trans Kreasindo Production Medan.